Volume 2: CFD and VIV 2015
DOI: 10.1115/omae2015-41695
|View full text |Cite
|
Sign up to set email alerts
|

Flow-Induced Vibrations of Single and Tandem Square Columns

Abstract: This work reports a set of numerical experiments to understand flow-induced vibrations of the square columns kept in a tandem arrangement. Results on the coupled force and response dynamics are presented for an isolated column and for a pair of square columns in the tandem configuration where downstream column is elastically mounted and free to oscillate in in-line and transverse directions. We assess the combined wake-induced and sharp-corner based galloping effects on the downstream column by comparing with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The existing studies on FIVs of two tandem square cylinders are summarized in table 1. So far, most of the existing studies on FIVs of two tandem cylinders have been concerned with the scenario where the upstream cylinder is fixed (Zhao et al 2015;Jaiman, Pillalamarri & Zhao 2016;Bhatt & Alam 2018;Han et al 2018;Yao & Jaiman 2019;Tamimi et al 2020). It was found that the wake of the upstream cylinder has a significant effect on the response of the downstream cylinder.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The existing studies on FIVs of two tandem square cylinders are summarized in table 1. So far, most of the existing studies on FIVs of two tandem cylinders have been concerned with the scenario where the upstream cylinder is fixed (Zhao et al 2015;Jaiman, Pillalamarri & Zhao 2016;Bhatt & Alam 2018;Han et al 2018;Yao & Jaiman 2019;Tamimi et al 2020). It was found that the wake of the upstream cylinder has a significant effect on the response of the downstream cylinder.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the wake of the upstream cylinder has a significant effect on the response of the downstream cylinder. For example, Zhao et al (2015) found that the shift of the stagnation point on the downstream cylinder, induced by the vortex shedding from the upstream cylinder, is responsible for the large-amplitude vibration of the downstream cylinder. Bhatt & Alam (2018) affirmed the significant role that the gap flow played in the vibration response of the downstream cylinder.…”
Section: Introductionmentioning
confidence: 99%